Aplikasi Regresi Logistik Biner dalam Pengidentifikasian Variabel-variabel yang Memengaruhi Perilaku Swamedikasi di Provinsi Gorontalo Tahun 2020 - Rizeka Ramadayanti; Sukim Sukim (Politeknik Statistika STIS, 2022)
Self-medication is a means of addressing health problems without visiting a doctor, and it is one of the reasons why people avoid outpatient care and health insurance. However, therapy errors may arise as a result of a lack of understanding, exacerbating the status of people with health difficulties. Every year, the number of people who does self-medication in Indonesia tend to be high. Gorontalo Province will have the highest self-medication rate in Indonesia in 2020, at 84.71 percent, despite having excellent health services. This study will look at the factors that influence self-medication behavior in Gorontalo Province in 2020, using Susenas Kor data from March 2020. For descriptive and inferential analysis, binary logistic regression and descriptive analysis were utilized. The results showed that the variables of age, education level, work status, home region, and health insurance ownership will have a substantial impact on self-medication behavior in Gorontalo Province in 2020.